2009
DOI: 10.1016/j.pharmthera.2009.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine signaling and the regulation of chronic lung disease

Abstract: Chronic lung diseases such as asthma, chronic obstructive pulmonary disease and interstitial lung disease are characterized by inflammation and tissue remodeling processes that compromise pulmonary function. Adenosine is produced in the inflamed and damaged lung where it plays numerous roles in the regulation of inflammation and tissue remodeling. Extracellular adenosine serves as an autocrine and paracrine signaling molecule by engaging cell surface adenosine receptors. Preclinical and cellular studies sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
121
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 100 publications
(125 citation statements)
references
References 173 publications
3
121
0
1
Order By: Relevance
“…These differences can be explained by pointing out that in the Ada 2/2 model, elevated levels of adenosine promote the destruction of the airway, but may also contribute to the heightened airway resistance. Indeed, several studies showed elevated levels of adenosine in the exhale condensate of patients with asthma that were thought to be responsible for the increased airway hyperresponsiveness reported in these patients (26). In addition, Ada 2/2 mice also present with lung fibrosis (19), which can also contribute to the increases in resistance and elastance and the reduction in compliance (18) reported here.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…These differences can be explained by pointing out that in the Ada 2/2 model, elevated levels of adenosine promote the destruction of the airway, but may also contribute to the heightened airway resistance. Indeed, several studies showed elevated levels of adenosine in the exhale condensate of patients with asthma that were thought to be responsible for the increased airway hyperresponsiveness reported in these patients (26). In addition, Ada 2/2 mice also present with lung fibrosis (19), which can also contribute to the increases in resistance and elastance and the reduction in compliance (18) reported here.…”
Section: Discussionsupporting
confidence: 50%
“…One molecule that is generated under these conditions of chronic inflammation, emphysema, and hypoxia is the signaling molecule adenosine (22,35). Elements of the adenosinergic signaling system are known to be elevated in chronic lung diseases, including COPD and IPF (26,27). However, little is known of how adenosine is able to orchestrate the remodeling of the vasculature leading to PH in COPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adenosine levels have been shown to increase in patients with asthma and COPD and in animal models having features of chronic airway disease (Zhou et al, 2009). Moreover, inhalation of adenosine induces bronchoconstriction in patients with asthma and COPD (Caruso et al, 2007).…”
Section: Adenosine Receptor Inhibitorsmentioning
confidence: 99%
“…Moreover, inhalation of adenosine induces bronchoconstriction in patients with asthma and COPD (Caruso et al, 2007). A non-selective adenosine receptor antagonist, theophylline, improves lung function and symptoms in asthma and COPD (Caruso et al, 2007;Zhou et al, 2009). Furthermore, adenosine receptors are expressed on most, if not all, inflammatory and stromal cell types involved in the pathogenesis of asthma and COPD.…”
Section: Adenosine Receptor Inhibitorsmentioning
confidence: 99%